Diálogos educacionais entre literatura infantil, educação científica e ambiental - Graciolli, Suelen Regina Patriarcha (2021)
This investigation was developed at the Graduate Program in Science Teaching at the Federal University of Mato Grosso do Sul (UFMS) and is linked to the line of research in Environmental Education. We problematize the relationship of Children's Literature in promoting dialogues between themes of socio-environmental and environmental relevance, and we define as a general objective, to analyze the possibilities of teaching work, involving Children's Literature for the construction of critical conceptions of Environmental and Scientific Education. With qualitative research and descriptive design, we investigated the possibilities of teaching work with teachers of Early Childhood Education, research subjects, through the focus group, memorial and the light of content analysis. Thus, we seek to understand the significant evidence to elucidate the object of investigation. Through data content analysis, we found four Categories of Analysis: Children's Literature as a promoter of dialogues between themes of relevance to children in the cultural and socio-environmental scope; The use of pedagogical strategies based on Children's Literature in childhood; Environmental Education and Science in Children's Literature; Persistent childhood experiences into adulthood. Data analysis also allowed us to build a Matrix for the analysis of Children's Literature with a focus on Environmental Education and Science Education, from the interpretation of the transcripts of the focus group, the bibliographical review on Scientific Literacy/Scientific Literacy, Environmental Education, and Children's literature, in addition to the categorization of theoretical contributions. We consider that the construction of a literature analysis instrument can, in a complementary way, help the teacher in the intention of choosing literature that brings children closer to the scientific universe. The memorial written by the teachers brought us deep reflections on the influence of our experiences in the construction of memories and how these memories influence our planning for the present and future. In this sense, we believe that it is necessary to think about the interrelationships between Children's Literature and other knowledge worked in the educational institution, because, based on literature, told, narrated or read, the child will interpret and create from the culture in that is inserted. In this way, we consider that the construction of children's knowledge is influenced by their experiences, and we believe that literature is fundamental for the development of imagination, emotions, and criticality, as well as contributing to the formation of free, autonomous, participatory, aware of themselves and the world in which they live.